Clearing Space for Multiple Voices: HIV Vulnerability amongst South Asian Immigrant Women in Toronto - Hawa, Roula; Chikermane, Vijaya (Atlantis, 2017)
This paper shares findings from a community-based research study conducted with South Asian women living with HIV in Toronto. Using qualitative methods, specifically in-depth interviews, participants’ experiences contribute to the creation of a more nuanced and intersectional understanding of HIV risk and support. Their narratives highlighted specific vulnerabilities growing out of structural inequities and gender-based power imbalances in their families and with their sexual and/or marital partners. The participants’ insights have important social justice and health program development implications.